Identification of a candidate dwarfing gene in Pallas, the first commercial barley cultivar generated through mutational breeding - Zakhrabekova, Shakhira; Chauhan, Pallavi; Dockter, Christoph; Ealumalai, Pavithra; Ivanova, Anastasiia; Jørgensen, Morten Egevang; Lu, Qiongxian; Shoeva, Olesya; Werner, Klaudia; Hansson, Mats (Frontiers in Genetics, 2023)
Many induced mutants are available in barley (Hordeum vulgare L.). One of the largest groups of induced mutants are the Erectoides (ert) mutants, which are characterized by a compact and upright spike and a shortened culm. One isolated mutant, ert-k.32, generated by X-ray treatment and registered in 1958 under the named “Pallas”, was the first ever induced barley mutant to be released on the market. Its value was an improved culm strength and enhanced lodging resistance. In this study we aimed to identify the casual gene of the ert-k.32 mutant by whole genome sequencing of allelic ert-k mutants. The suggested Ert-k candidate gene, HORVU.MOREX.r3.6HG0574880, is located in the centromeric region of chromosome 6H. The gene product is an alpha/beta hydrolase with a catalytic triad in the active site composed of Ser-167, His-261 and Asp-232. In comparison to proteins derived from the Arabidopsis genome, ErtK is most similar to a thioesterase with de-S-acylation activity. This suggests that ErtK catalyzes post-translational modifications by removing fatty acids that are covalently attached to cysteine residues of target proteins involved in regulation of plant architecture and important commercial traits such as culm stability and lodging resistance.